Management of pediatric hemolytic uremic syndrome - Bora Gülhan; Fatih Özaltın; Kibriya Fidan; Zeynep Birsin Özçakar; Oğuz Söylemezoğlu (The Turkish Journal of Pediatrics)
Classical clinical triad of hemolytic uremic syndrome (HUS) is microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury associated with endothelial cell injury. Several situations, including infections, medications, malignancies, and transplantation can trigger endothelial damage. On the HUS spectrum, atypical hemolytic uremic syndrome (aHUS) deserves special attention in pediatric patients, as it can cause end-stage kidney disease and mortality. A dysfunction in the alternative complement pathway, either acquired or genetic, has been shown to be the main underlying cause. In the last decades, breathtaking advances have been made in understanding the pathophysiology of this rare disease, which has led to more efficient treatment. Recent studies have implicated genes in pathways beyond the alternative complement system, such as DGKE, TSEN2, and INF2 highlighting the importance of personalized management. Eculizumab has brought about dramatic improvements in the treatment of aHUS. Beyond eculizumab, there are many alternative therapeutics in the pipeline that target the complement system. Because of the rarity of aHUS, data from multiple patient registries are very important. The present report aimed to summarize the most important aspects of diagnosing and treating aHUS based on the Turkish national registry and the literature so as to improve clinical practice.